Statement of the AGO and AG-CPC on the Aftercare/Follow-up for Surgical Procedures of the Lower Genital Tract after the Introduction of a New Cancer Screening Guideline - Hillemanns, Peter; Tempfer, Clemens; Beckmann, Matthias; Kueppers, Volkmar; Quaas, Jens (Geburtshilfe und Frauenheilkunde, 2020)
The new guideline on organized cancer screening programs has been in force in Germany since January 1st, 2020. The guideline has amended earlier recommendations on cytological examinations, which were previously carried out annually during screening. The guidelines-based recommendations on the appropriate follow-up for preinvasive and invasive lesions of the uterine cervix and endometrium are briefly outlined and differentiated from screening cytology and Pap/HPV co-testing as described in the guideline on organized cancer screening programs (oKFE-RL).
CRIS-Team WoS Importer:2020-09-11